Team working training in the digital transition: skills, strategies, and pedagogical challenges - Emanuele Serrelli (Formare, 2025)
The transformations of today’s work environments, characterized by digitalization, cultural diversity, and continuous change, pose new challenges for teamwork and, consequently, for training. On the one hand, the maps of required skills and new training strategies for working in complex, interconnected, yet unstable environments are becoming increasingly sophisticated; on the other hand, critical doubts arise about the prevailing approaches, often focused solely on technical learning and individual adaptation to workplace standards. Undoubtedly, strategies such as continuous feedback, experiential learning, and rubrics for evaluating teamwork skills contribute to creating the conditions for the emergence of teams that will be capable of effectively and reliably addressing future challenges. However, there is a risk of tying these techniques to a performative and instrumental vision. Much of the pedagogical tradition calls for resistance to this view, instead promoting the group as an educational and human context, capable of fostering belonging, personal growth, and connection, a laboratory of relationships that ultimately supports democratic participation and collective well-being.